Analisis Exergy Mesin Gas Pusat Listrik Pltmg Balai Pungut 7 X 15 Mw - Risnawati, Kinkin; Romy, Romy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
PLTMG have an efficiency increase of between 30-50%. This value is still not optimal because the utilization is less efficient. The engine is more often operated, the engine need maintenance for better performance. The decrease inengine performance produces wasted energy so that engine efficiency is not optimal. In addition, the maintenance process takes a long time until the engine can be operated again. This is a problem because the maintenance process iscarried out on all cylinder engines. The purpose of this research are for calculating, analysing and testing of exergy destroyed in the cylinder unit of the Balai Pungut PLTMG gas fuel unit 4. From the analysis, the biggest efficiency ofenergy is before overhaul which is 46,3 %.Keywords : dual fuel, energy, exergy, engine, efisiensi energy